MODELING OF SEPTIC TANKS SEEPAGE NEAR DUG WELLS IN MARGAHAYU VILLAGE, BANDUNG REGENCY - Dedi Mulyadi; Rizka Maria; Khori Sugianti; Arifan Jaya Syahbana (Widyariset, 2018)
Dense settlements have an impact on pollution, one of which is domestic pollution which results in groundwater and soil water pollution at ground level. Identification of pollution that occurs below the soil surface (groundwater contamination) is more difficult to detect, so modeling is needed to find out how the rate of groundwater pollution rate. Modeling is done by using water sampling method at dug well at location adjacent to septic tank. Sampling ground water and infiltration modeling is done by using Geostudio SEEP/W software. The research area is in Margahayu village, Bandung regency. The results of laboratory analysis and physical observation in the field show that the Margahayu region has ammonium (NH4-N) content which is above the standard quality threshold. This condition is reinforced by modeling simulation results that there has been domestic sewage from septic tanks to dug wells. Pollution has reached groundwater level with depth ranged between 4-5 meters. The distance of wells adjacent to the septic tanks affects the quality of groundwater. In the KB area 17 it is indicated that the contamination in the residents' wells in harike-3i, KB new on the 32-40 day time frame, and KB new 2 on the 24th day. Distance sources of contaminants and soil permeability play an important role in determining the travel time of contaminants.